Pengaruh Live Streaming, Discount, Customer Trust Terhadap Impulsive Buying di Tiktok Shop: Survey pada Masyarakat Kota Surabaya, Jawa Timur - Audina Farah Dewintha Tuapattinaya; Siti Ning Farida (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine and analyze the influence of live streaming, discounts, customer trust on impulsive buying at TikTok Shop, both simultaneously and partially. This research uses the independent variable (X), namely Live Streaming, Discount, Customer Trust and the dependent variable (Y), namely Impulsive Buying. This research uses an associative quantitative method with a purposive sampling technique of 110 respondents who use the TikTok Shop application. The data collection method uses a questionnaire. Instrument testing uses validity and reliability tests and the test results show that the entire instrument is declared valid and reliable. The data analysis technique uses multiple linear regression, classical assumption test, f test and t test. The results of this research are that partially "Live Streaming and Customer Trust" have a significant and positive influence, while the Discount variable has no significant influence on Impulsive Buying in the TikTok Shop. And simultaneously Live Streaming, Discounts, Customer Trust have a significant and positive effect of 51.7% on Impulsive Buying on TikTok Shop.